Emission of some rare gases at the Los Azufres, Mexico, geothermal reservoir - Mario César Suárez Arriaga (Geofísica Internacional, 2002)
The chemistry of fluids in the Los Azufres, Mexico geothermal field originated from volcanic processes and is controlled by temperatures at depth, mineral solubility, pH values and mineral equilibrium. Vapor phase at this reservoir has an heterogeneous composition. It shows a wide range of non‑condensible gases (NCG) concentration, which ranges between 1% and 9% of total gas weight in the steam phase. NCG are routinely measured in this reservoir and typically contain CO2 , H2S, NH3 , CH4 , O2 , H2 , He, N2 and Ar; although there are also Ne, Kr and Xe, but these gases are not registered. Carbon dioxide is the major constituent found in the field, representing between 70% and 99% of total NCG weight. The highest CO2 content is found in shallow wells with high steam quality. H2S is the second most important gas, varying between 0.2% and 13% in the total weight. Simultaneously to fluid extraction, significant amounts of cold liquid and air are injected into the reservoir, modifying its natural geochemistry. Total gas concentration found in some wells are increased because of the extra amount of atmospheric N2 and Ar injected. The molar quotient N2 /Ar has been falling with time reaching in some cases the same value as in the atmosphere. Both gases are pushing the NCG changing their natural spatial distribution. The thermodynamic effect of reinjection has been beneficial for the energy production and longevity of this geothermal field. Rare gases such as He and Ar measured in this field show a low, but general trend to increase when the corresponding wells are subjected to continuous production, with few unusual exceptions. Apparently, such increment is proportional to the amount of fluid extracted and to the time of extraction. But, in other cases, the dependence of both gases on production is not clear. In this paper the observed evolution and spatial distribution of NCG and of those two rare gases at the Los Azufres geothermal field are reported for the period 1981‑1999.